Sowjetische Grafik der Sammlung Ludwig. - Becker, Wolfgang (Aachen : Neue Galerie - Sammlung Ludwig Aachen, 1990)
Abramisvili, Merad ; Abramova, Olga Michailovna ; Achunov, Masabich Fatchulislamovic ; Alymov, Aleksandr Sergeevic ; Ancane, Baniuta ; Arrak, Jurij ; Atlanov, Jurij Michailovic ; Azimov, R.A. ; Bacurin, Evgenij Vladimirovic ; Bedina, Alla Igorevna ; Begma, Vladimir ; Bejsembinova, Elena Sergeevna ; Beljanov, Nikolaj ; Bicjunas, Rimas ; Birstejn, Maks ; Bisti, Dimitrij Spiridanovic ; Blagovolin, Nikolaj Nikdaevic ; Bolsakova, Irina Ivanovna ; Borodin, Anatolij Vladimirovic ; Bugaeva, Galina ; Burganov, Aleksandr ; Burkokas, Ionas ; Carysnikov, Ju I. ; Cereteli, Georgij ; Chait, T.F. ; Chelmut, Ivan Sanovic ; Chodzakuliev, Nurat ; Chudajberdaev, Annaklyc ; Cigal, Viktor Efimovic ; Cincadze, Nana ; Cirulis, Karl Petrovic ; D'jakov, Vladimir ; Davydov, A.S. ; Demko, Adol'f Ivanovic ; Dergileva, Elena ; Deviseva, N. ; Dolendzasvili, Guram Nikolaevic ; Ëel'ma, Cheral'd Villenovic ; Ëel'ma, Ynneleid Astrid ; Emmus, Julo ; Favorskij, N.W. ; Fejgin, Moisej Izenailevic ; Finkel'stern, David ; Gadziev, A.A. ; Gannuskin, Evgenij ; Gennadiev, Andrej ; Geta, Sergej ; Glonti, G.L. ; Golicyn, Illarion Vladimirovic ; Graziene, D. ; Grecina, Olga Nikolaevna ; Gricjuk, Nikolaj Demianovic ; Gurbanov, Gurbangel'di ; Gutman, Naftolij ; Ionkajtite, Danute ; Ivanov, Viktor Ivanovic ; Ivanova, Galina ; Jachnin, O. Ju. ; Jakovlev, Jakov Jakovlevic ; Jankilevskij, Vladimir ; Jansone, Biruta ; Jovaisiene, Vida ; Juksine, Mar'e ; Kagarov, Medad Ajtachunovic ; Kal'pus, A. ; Kalinin, Viktor ; Kalinyceva, Klara Ivanovna ; Kalita, Nikolaj Ivanovic ; Kaplan, Anatolij Lvovic ; Kepezinskas, Rimvidas ; Kjutt, Alleks Voldemarovic ; Klar, Konkordija A. ; Knjazev, Sergej ; Komov, O.K. ; Konstantinov, Fedor Denisovic ; Korotkova, E.A. ; Kostin, A.L. ; Krylov, Porfirij Nikititis ; Kucas, Antanas ; etc.
Sowjetische Grafik der Sammlung Ludwig, Neue Galerie - Sammlung Ludwig, Aachen, 26.1.1990 - 11.3.1990
Duits
boek
Keywords: U.S.S.R.